국내 유방암 환자의 우울 중재 프로그램의 효과: 체계적 문헌고찰과 메타분석 - 박현주(Park, Hyun-Joo); 손혜경(Son, Hye Gyeong) (Asian oncology nursing, 2020)
Purpose: This study aims to investigate and collect literature related to the effects of depression intervention programs on depression of breast cancer patients in Korea, and review these precedent studies on the effectiveness of depression intervention programs through meta-analysis. Method: To achieve a systematic literature review, a review question was defined according to PICO-SD: “How do depression intervention programs affect depression reduction in breast cancer participants compared to the control group?” The subjects of this study were research papers on depression intervention programs, which were released in Korea between 1990 and February 2020. Through the literature quality assessment in accordance with the SIGN (2012) Guidelines on Quality Assessment, a total of 30 pieces were selected as the final subjects of this study. Result: The overall effect size of a total of 30 pieces was -3.92 (95% CI: -4.82, -3.03, p<.001), which indicates that these depression intervention programs have a great effect on depression reduction. Conclusion: Intervention in depression of breast cancer patients in Korea is considered to contribute to improving the quality of their life and the ability to manage their symptoms, thus helping them have a positive meaning of life. KCI Citation Count: 0